Política pública de saúde do trabalhador: o programa de atenção integral ao alcoolista e outros dependentes químicos na universidade federal da Paraíba - Lima, Fernando Antonio de (2017)
The objective of this research is to analyze the experience of PAIAD (Full Care to Alcoholic and other drug addicts Program) at Federal University of Paraiba, and its contributions to the health of the University employees. Presently inactive, PAIAD was founded in 1993 by the University Super-intendance of Human Resources, with the aim of helping University employees who were addicted to alcohol. This study was developed through a documental research, together with semi-structured interviews with individuals who had participated in the creation and/or activities of the Program, as well as with managers from the Personnel Management Pro-Rectory (PROGEP) and the University Coordination of Life Quality, Health and Security of the Worker (CQVSST). Data were analyzed within a qualitative approach, and the discussion was developed through Contents Analysis. Results show the relevance of PAIAD, beyond the university boundaries, and also, the importance of rescuing many of the initiatives of this relevant Program, which is a reference in the policy of health care to the University employees, with special attention to the problem of abusive consumption of alcohol and other psychotropic substances.